Kedudukan Sumpah Pada Alat Bukti Keterangan Saksi Palsu dalam Proses Perkara Pidana - Ardellia Luckyta Putri Armunanto; I Made Sepud; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2019)
Eyewitness is one tool evidence is crucial in the process of proof at this stage of the review. A witness sworn or promised mandatory before or after he gave his statement at trial. Giving false information is a criminal offense regulated in Article 242 of the Criminal Code. Formulation of the problem in the writing of this research are: 1) how is the position of the oath against false witnesses in a criminal proceeding? and 2) how will criminal sanctions against witnesses who give false information in the process of criminal cases?. The type of research used in the writing of this is normative and legal research using approach problem in the form of a statutory approach, the conceptual approach and the approach to the case using legal materials in the form of source material the law of primary, secondary, and tertiary. Legal materials collection technique is done by way of reading, gathering and documentation. Analysis of legal materials used i.e. descriptive analysis that refers to a particular problem and is associated with the opinion of the experts, legislation and break it in the form of a research. The position of the oath on the false witnesses in a criminal proceeding is not considered a valid instrument of evidence, so that the information has no value the power of proof. Criminal sanctions against witnesses who give false information in the process of criminal cases will be subject to imprisonment for seven to nine years in accordance with Article 242 of the book the laws of criminal law.